INVESTIGATION OF SFLT-1 AND VEGF EXPRESSION IN NORMOTENSIVE AND PREECLAMPTIC PLACENTA. AN IMMUNOHISTOCHEMICAL STUDY - Ugur Seker (Rojan GÜMÜŞ, 2020)
Objectives: The pathogenesis of preeclampsia is still not clear, but endothelial dysfunction believed to be one of the most encountered problems during placenta development in preeclamptic patients. Both vascular endothelial growth factor (VEGF) and its antagonist, soluble Fms-Like tyrosine kinase-1 (sFlt-1), have roles in vascular function. In this study, we have investigated immunohistochemical expression of VEGF and sFlt-1 in term placenta of normotensive and preeclampsia patients. Methods: Totally twenty term placentas were obtained from pregnant women of which 10 preeclampsia patient and 10 normotensive. Placentas were dissected and tissue samples were subjected to routine tissue processing protocol, then embedded in paraffin blocks. Serial sections were obtained from paraffin blocks and stained with H&E and PAS for routine histopathology. VEGF and sFlt-1 immunohistochemistry was performed to the sections. Results: When compared to control group, severe pathological changes were observed in preeclamptic placentas. Increase in number of syncytial knots and intervillous bridges, hemorrhage in interstitium, dilatation and congestion in villous capillaries, increase in fibrin accumulation in villus stroma, and increase in thickening of basement membrane were very clear. VEGF expression was significantly higher in normotensive placentas compared to preeclamptic. On the other hand, sFlt-1 expression was significantly increased in preeclamptic placentas. Conclusions: When the VEGF and sFlt-1 expression was considered, higher expression of sFlt-1 at preeclampsia, but decrease in VEGF expression, might be related to endothelial dysfunction in preeclampsia. Overall, this study demonstrates, imbalance between VEGF and sFlt-1 is one of the major reason of endothelial dysfunction in preeclamptic placenta.